Disaccharide uptake and priming in animal cells: inhibition of sialyl Lewis X by acetylated Gal beta 1-->4GlcNAc beta-O-naphthalenemethanol. - Sarkar, A K (1995)
Inhibitors of glycosylation provide a tool for studying the biology of glycoconjugates. One class of inhibitors consists of glycosides that block glycoconjugate synthesis by acting as primers of free oligosaccharide chains. A typical primer contains one sugar linked to a hydrophobic aglycone. In this report, we describe a way to use disaccharides as primers. Chinese hamster ovary cells readily take up glycosides containing a pentose linked to naphthol, but they take up hexosides less efficiently and disaccharides not at all. Linking phenanthrol to a hexose improves its uptake dramatically but has no effect on disaccharides. To circumvent this problem, analogs of Xyl beta 1-->6Gal beta-O-2-naphthol were tested as primers of glycosaminoglycan chains. The unmodified disaccharide did not prime, but methylated derivatives had activity in the order Xyl beta 1-->6Gal(Me)3-beta-O-2-naphthol > Xyl beta 1-->6Gal (Me)2 beta-O-2-naphthol >> Xyl beta 1-->6Gal(Me)beta-O-2-naphthol. Acetylated Xyl beta 1-->6Gal beta-O-2-naphthol also primed glycosaminoglycans efficiently, suggesting that the terminal xylose residue was exposed by removing the acetyl groups. The general utility of using acetyl groups to create disaccharide primers was shown by the priming of oligosaccharides on peracetylated Gal beta 1-->4GlcNAc beta-O-naphthalenemethanol. This disaccharide inhibited sialyl Lewis X expression on HL-60 cells.